Chemical Pesticides and Human Health: The Urgent Need for a New Concept in Agriculture - Nicolopoulou-Stamati, Polyxeni; Maipas, Sotirios; Kotampasi, Chrysanthi; Stamatis, Panagiotis; Hens, Luc (Frontiers in Public Health, 2016)
The industrialization of the agricultural sector has increased the chemical burden on natural ecosystems. Pesticides are agrochemicals used in agricultural lands, public health programs, and urban green areas in order to protect plants and humans from various diseases. However, due to their known ability to cause a large number of negative health and environmental effects, their side effects can be an important environmental health risk factor. The urgent need for a more sustainable and ecological approach has produced many innovative ideas, among them agriculture reforms and food production implementing sustainable practice evolving to food sovereignty. It is more obvious than ever that the society needs the implementation of a new agricultural concept regarding food production, which is safer for man and the environment, and to this end, steps such as the declaration of Nyéléni have been taken.